Electron–phonon coupling and coherent energy superposition induce spin-sensitive orbital degeneracy for enhanced acidic water oxidation - Yanfeng Shi; Lupeng Wang; Miao Liu; Zuozheng Xu; Peilin Huang; Lizhe Liu; Yuanhong Xu (Nature Communications)
Abstract The development of acid-stable water oxidation electrocatalysts is crucial for high-performance energy conversion devices. Different from traditional nanostructuring, here we employ an innovative microwave-mediated electron–phonon coupling technique to assemble specific Ru atomic patterns (instead of random Ru-particle depositions) on Mn0.99Cr0.01O2 surfaces (RuMW-Mn1-xCrxO2) in RuCl3 solution because hydrated Ru-ion complexes can be uniformly activated to replace some Mn sites at nearby Cr-dopants through microwave-triggered energy coherent superposition with molecular rotations and collisions. This selective rearrangement in RuMW-Mn1-xCrxO2 with particular spin-differentiated polarizations can induce localized spin domain inversion from reversed to parallel direction, which makes RuMW-Mn1-xCrxO2 demonstrate a high current density of 1.0 A cm−2 at 1.88 V and over 300 h of stability in a proton exchange membrane water electrolyzer. The cost per gallon of gasoline equivalent of the hydrogen produced is only 43% of the 2026 target set by the U.S. Department of Energy, underscoring the economic significance of this nanotechnology.